Bias corrections for moment estimators in Poisson INAR(1) and INARCH(1) processes - Weiß, Christian; Schweer, Sebastian (Statistics & probability letters, 2016)
For Poisson INAR(1) or INARCH(1) count data time series, explicit asymptotic approximations for bias and standard deviation of common moment estimators are derived. Their finite-sample performance is shown by simulations. Bias corrected estimators are applied within examples.